Pelatihan Penanganan Kebocoran Tabung Gas Untuk Mengurangi Kecemasan Masyarakat - Marpaung, Noveri; Hutabarat, Sakti; Ervianto, Edy; Nurhalim, Nurhalim; Amri, Rahyul; Hidayat, Hendra; Jawad, Abdul; Abdi, Reynaldi Putra; Putra, Dandi Kelana; Putri, Utari Cahyani; Ramadhani, Suci; Mukminin, Silakhul; Putri, Elvina; Jaufia, Syakira Aqra; Manfaah, Siti Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Nowadays, a gas stove is a basic need in every household because it is Government’s Program to convert conventional stove to be gas stove. LPG Gas and its holder are inseparably parts when using gas stove. Even using stove gas has been a compulsion for society for the last many years, however, spark, explosion and fire still happens that are caused by using a gas stove/holder. These circumstances create worry for its users. Therefore, students from the University of Riau under Community Service Program perform training to help the community not be afraid/worry when using stove gas in Sukadamai Village from Bangsal Aceh County in Dumai City – Riau Province. Aim of this service is to educate people in using LPG gas stove or holder and the way to handle the leakage of its LPG gas holder in the right way to overcome any danger if it happens in Sukadamai Village from Bangsal Aceh County. The results of this training show that communities are braver to use gas stoves because at this time they understand how to use the gas stove in the right way and how to handle any danger that could happen. By this training, hopefully people in Sukadamai Village from Bangsal Aceh County are not afraid/worried anymore when using LPG gas stove/holder.